The Relaxation Response Resiliency Enhancement Program in the Management of Chronic Refractory Temporomandibular Joint Disorder: Results from a Pilot Study. Issue 3 (September 2013) - Vranceanu, Ana-Maria; Shaefer, Jeffery R.; Saadi, Ashkan Fahandej; Slawsby, Ellen; Sarin, Jaya; Scult, Matthew; Benson, Herbert; Denninger, John W.
Abstract Objectives: This is an open-pilot study to evaluate the feasibility, acceptability and efficacy of a pain-specific version of an established mind–body medicine program, the Relaxation Response [RR] Resiliency Program [R3P], in patients with chronic temporomandibular disorder [TMD]. Methods: Male and female with at least a six-month history of pain involving the masticatory muscles were sought in the Orofacial Pain Centers of the Massachusetts General Hospital [MGH] or through an advertisement sent to MGH employees from 2008 to 2010. Eligible participants underwent the R3P intervention [eight group sessions] after standard medical management. Pre- and post-group patients underwent objective measures of impairment [vertical and lateral range of motion with and without pain, temporomandibular joint and muscle pain palpation, and algometer measures] and completed psychosocial measures [Symptom Severity Index, Perceived Stress Scale, the Symptom Checklist-90-Revised and Short Form 36 Health Survey]. Results: Twenty-four subjects [16 females, 90% from MGH Orofacial Pain Centers, 10% from among MGH employees], mean age 38 years, met eligibility criteria and participated in the study. The intervention was highly feasible and accepted by patients, as evidenced by a 92% rate of completion. Paired t-test analyses revealed improvement on self-reported pain measures: pain intensity [p < 0.02], pain frequency [p < 0.002], pain duration [p < 0.027], pain tolerability [p < 0.009] and on several objective tests. Conclusions: The pain specific R3P is efficacious in reducing objective and subjective symptoms in patients with chronic refractory TMD. The comprehensive intervention, which combines educational information about pain with RR, cognitive behavioral and resiliency-enhancement skills, is accepted by patients and may be more efficacious than other treatments with fewer elements.